2015
DOI: 10.1001/jamaoncol.2015.0829
|View full text |Cite|
|
Sign up to set email alerts
|

Statin Use at the Time of Initiation of Androgen Deprivation Therapy and Time to Progression in Patients With Hormone-Sensitive Prostate Cancer

Abstract: Importance Statin use has been associated with improved prostate cancer outcomes. Dehydroepiandrosterone sulfate (DHEAS) is a precursor of testosterone and a substrate for SLCO2B1, an organic anionic transporter. We previously demonstrated that genetic variants of SLCO2B1 correlated with time to progression (TTP) on androgen deprivation therapy (ADT). Objective Since statins utilize SLCO2B1 to enter cells, we hypothesized that they may compete with DHEAS uptake and that statin use might prolong TTP while on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 30 publications
7
82
0
Order By: Relevance
“…Evidence suggests that decreasing serum cholesterol slows prostate tumor development, at least in part, due to reductions in the uptake of androgens and androgen precursors into prostate tumor tissues [31]. The human bile acid pool undergoes enterohepatic recirculation, which occurs multiple times per meal.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that decreasing serum cholesterol slows prostate tumor development, at least in part, due to reductions in the uptake of androgens and androgen precursors into prostate tumor tissues [31]. The human bile acid pool undergoes enterohepatic recirculation, which occurs multiple times per meal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study comparing pre-operative and postoperative use of statins in 2,137 Korean men who underwent radical prostatectomy between 1998 and 2011 found that postoperative statin use prolonged recurrence-free survival over a median follow-up period of 32 months, especially in patients with high-risk disease (Gleason score ≥7; HR 0.27; 95% CI 0.13–0.59; P = 0.001), but preoperative statin use did not change pathological outcomes 107 . Finally, one study with a median follow-up time of 70 months reported that statin use significantly prolonged time to progression in 926 men receiving androgen deprivation therapy, even after adjusting for known prognostic factors such as biopsy-based Gleason score, type of primary therapy and presence of metastases at initiation of androgen deprivation (HR 0.83; 95% CI 0.69–0.99; P = 0.04) 108 .…”
Section: Combination With Prostate Cancer Therapiesmentioning
confidence: 99%
“…These SLCO2B1 variants result in increased DHEA transport into cells. Statins are recognized inhibitors of SLCO2B1 transport and may explain why a longer time to progression for men treated with a statin at the time of ADT initiation was seen in a large cohort of men receiving ADT (Harshman et al 2015). This was seen in men with and without metastases after adjusting for prognostic factors.…”
Section: Genomic Alterations Implicating Sex Steroids In Prostate Canmentioning
confidence: 99%